Tiktok sebagai Sumber Informasi Politik dan Dampaknya terhadap Partisipasi Politik Generasi Z dalam Musyawarah Desa: Studi Kasus Desa Kincang Kecamatan Rakit Kabupaten Banjarnegara - Ibnu Kowimudin; Supartinah (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The development of social media has transformed patterns of political communication and participation, including at the village level. This study aims to analyze the role of TikTok as a source of political information and its impact on Generation Z’s political participation in the Village Deliberation Forum in Kincang Village, Banjarnegara Regency, which remains dominated by older age groups. This research employs a qualitative approach with a case study design, using in-depth interviews, observation of village deliberations, and documentation. Data were analyzed using Miles and Huberman’s interactive model. The findings indicate that TikTok serves as an initial gateway to political literacy for Generation Z through visual and easily accessible content, thereby increasing political awareness and political efficacy. However, the brief nature of TikTok content may lead to partial understanding, making the Village Deliberation Forum a crucial space for clarification and contextual learning. This study highlights the integration of digital public spaces and formal deliberative institutions as a novel contribution to strengthening youth political participation at the village level.